4 Non-contrast assessment of myocardial viability in chronic myocardial infarction by native T1 and T2 mapping at 1.5T CMR: comparison with late gadolinium enhancement technique. (18th May 2017) - Dastidar, Amardeep Ghosh; Pontecorboli, Giulia; Harries, Iwan; Moret, Charlie; Morgan, Gareth; Garate, Estefania De; Baritussio, Anna; Bucciarelli-Ducci, Chiara
Abstract : Background: Viability assessment is a key aspect in the management of ischaemic heart disease (IHD). Hypothesis: native T1 and T2 mapping can assess myocardial viability without the use of gadolinium. Methods: 30 patients with known MI (>5yrs from MI) and 20 normal healthy controls underwent conventional 1.5T CMR to assess LV function and the presence and extent of myocardial infarction (scar transmurality) using a scale of 0–4 for the 16 AHA segment (0=no scar, 1=1–24%, 2=25–49%, 3=50–74% and 4 ≥75% scar thickness). Segments with <50% LGE was considered viable. LGE viability was compared with the corresponding native segmental T1 and T2 obtained from T1 maps (MOLLI sequence, motion corrected) and T2 maps. Results: 800 myocardial segments were analysed (320-healthy controls, 480-MI patients). The mean segmental T1 and T2 values for scar transmurality grade 0–4 were 1031±31 ms, 1070±33 ms, 1103±32 ms, 1164±58 ms, 1206±118 ms (p<0.001) and 52±4 ms, 55±4 ms, 58±5 ms, 59±8 ms, 66±9 ms (p<0.001) respectively in chronic MI. ROC analysis of 480 ?segments in chronic MI showed that for myocardial viability assessment, native T1-mapping demonstrated excellent diagnostic performance compared to LGE as the gold standard (AUC-0.94, 95%CI 0.89–0.99, p<0.0001). Native T1 mapping also had the highest diagnostic accuracy for viability assessment when compared to T2 mapping, LV wall thickness, regional wall motion abnormality. A T1 threshold of 1090ms best ?differentiated viable from non-viable segments with a sensitivity of 90% and specificity of 91%. Conclusions: Native T1 mapping can differentiate between normal, viable, and non-viable myocardium with distinctive T1 profiles in chronic MI without the need for gadolinium.